Theoretical and Methodological Approaches on the Intellectual Capital - Rus, Alexandra Ioana Daniela; Achim, Monica Violeta; Borlea, Sorin Nicolae (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
The aim of this paper consists in providing a general overview of the notion of intellectual capital as a key to maximizing the corporate performance. Following the researches carried out, we present the delimitations of the intellectual capital in relation with human capital, relational capital and structural capital. In terms of its measurement, we focus on a question which could be a solid base for the next studies: "Can intellectual capital be evaluated?" In this regard, a number of methods (direct and methods based on assets returns), generic model and individual company models were presented, concluding in this way with a hierarchy in terms of utility and their importance.